Combined effects of multiple risk factors on asthma in school-aged children. (December 2017) - Szentpetery, Sylvia S.; Gruzieva, Olena; Forno, Erick; Han, Yueh-Ying; Bergström, Anna; Kull, Inger; Acosta-Pérez, Edna; Colón-Semidey, Angel; Alvarez, Maria; Canino, Glorisa J.; Melén, Erik; Celedón, Juan C.
Abstract: Background: Little is known about synergistic effects of several risk factors on asthma. We developed a risk score in Puerto Rican children, and then used this score to estimate the combined effects of multiple risk factors on asthma at school age in Puerto Rican and Swedish children. Methods: Case-control study in 609 Puerto Rican children (aged 6–14 years) and longitudinal birth cohort study of 2290 Swedish children followed up to age 12 years (The Children, Allergy, Milieu, Stockholm, Epidemiological Survey [BAMSE] Study). In both cohorts, there was data on parental asthma, sex, obesity, allergic rhinitis, and early-life second-hand smoke (SHS); data on diet and (in children ≥9 years) lifetime exposure to gun violence were also available in the Puerto Rico study. Asthma was defined as physician-diagnosed asthma and ≥1 episode of wheeze in the previous year. Results: In a multivariable analysis in Puerto Rican children, male sex, parental asthma, allergic rhinitis, early-life SHS, an unhealthy diet and (in children ≥9 years) gun violence were each significantly associated with asthma. We next created a risk score using these variables (range, 0 to 5-6 in Puerto Rico and 0 to 4 in BAMSE). Compared with Puerto Rican children without any risk factors (i.e. a score of 0), Puerto Rican children with 2, 3, and at least 4 risk factors had 3.6 times (95% CI = 1.4–9.2), 10.4 times (95% CI = 4.0–27.0), and 21.6 times (95% CI = 7.2–64.9) significantly higher odds of asthma, respectively. In BAMSE, the presence of 2, 3, and at least 4 risk factors was significantly associated with 4.1 times (95% CI = 2.3–7.4), 6.3 times (95% CI = 3.0–13.3), and 17.2 times (95% CI = 4.1–73.2) increased odds of asthma at age 12 years. Conclusions: Our findings emphasize the multifactorial etiology of asthma, and suggest that concurrent eradication or reduction of several modifiable risk factors may better prevent or reduce the burden of childhood asthma. Highlights: Little is known about synergistic effects of multiple risk factors on asthma. We developed a risk score in a case-control study of Puerto Rican children. This score was used to estimate the combined effect of multiple risk factors on asthma in Puerto Rican and Swedish children. The presence of ≥4 risk factors was associated with 16- to 25-fold higher odds of asthma in Puerto Rican and Swedish children. Interventions or policies addressing several risk factors may be better in asthma prevention than single-factor interventions. Abstract : The presence of four or more risk factors was significantly associated with 16-times to 25-times increased odds of asthma at school age in Puerto Rican and Swedish children.